Food, gastronomy, sustainability, and social and cultural development cross-disciplinary perspectives
"Food, Gastronomy, Sustainability, and Social and Cultural Development analyzes the relationship between gastronomy and sustainability from a sociocultural perspective. It uses practical case studies to reveal the connection between food, society, culture, and the impact they have with each other. Beginning with the introduction of the relationship among gastronomy, sustainability, culture, and contemporary controversies, this book expands topics from binomial gastronomy at local level, impact of sustainability on gastronomic experiences, an evaluation of production systems to the role of gastronomy, and sustainability in tourism. The role of technology in food and sustainability, health, ideologies, and social movements surrounding gastronomy are also widely discussed. This book is a valuable reference for food scientists, undergraduate and graduate students, and industrial professionals working in the food processing field." --